Coal gasification fine slag doped g-C3N4 photocatalyst as well as preparation method and application thereof
By mixing the fine dregs of gas-based gas-based gas to the surface of the G-C3N4, the CGFS/G-C3N4 photocatalyst is constructed, which solves the problem of the existing G-C3N4 photocatalyst. Significantly improve the effect of optical catalytic performance and degradation efficiency.
Patent Information
- Application Number
- CN202411522305.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-01-28
AI Technical Summary
When using graphite phase carbon nitride (g-C3N4) as the photocatalyst, the prior art has problems of unsatisfactory photocatalytic activity and visible light utilization efficiency, especially when degrading methylene blue dyes.
By mixing the il -ified fine residue (CGFS) to the surface of the G-C3N4, the CGFS/G-C3N4 photocatalyst is constructed to improve the optical catalytic performance with its good pore structure and high content of residual carbon.
It significantly improves the performance and stability of the photocatalytic and stable performance, effectively degrades the sub -base blue under the visible light, improves the degradation efficiency, and widen the use of gas to dregs.
Smart Images

Figure CN119368216A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of photocatalysts, and in particular relates to a coal gasification fine slag doped g-C3N4 photocatalyst and a preparation method and application thereof. Background Art
[0002] Organic dye wastewater refers to the wastewater generated by the dyes and related auxiliaries used in industrial production after the dyeing process. The wastewater has complex components, high organic content and deep chromaticity. A small amount can pollute the color of the water. This pollution will not only impact the visual system of humans or animals, but also affect the photosynthesis of green plants in the water, thereby threatening the survival of organisms in the water, and may even cause mass death of organisms. Among them, methylene blue is one of the widely used organic dyes. Although the methylene blue in the methylene blue wastewater is not toxic itself, it may cause harm to the human body if used improperly, such as long-term or large-scale use. For example, it may cause allergic reactions, gastrointestinal reactions, nervous system symptoms, blood system symptoms, and cardiovascular system symptoms.
[0003] Photocatalytic degradation is an effective method for treating organic dye wastewater. Graphite phase carbon nitride (g-C3N4) is a non-metallic inorganic semiconductor with good chemical and thermal stability, low cost, safety and non-toxicity, and is used in the field of photocatalysis. However, due to its own band structure and its high photogenerated electron-hole recombination rate, the single g-C3N4 material has disadvantages such as its own high photocatalytic activity and visible light utilization efficiency. The prior art, such as application publication number CN105195203 A, uses a simple and rapid thermal polymerization method to synthesize niobium pentoxide and graphite-like carbonized nitrogen heterojunction photocatalyst in one step, which can be used to degrade methylene blue dye under visible light; but the doping raw material niobium pentoxide used is relatively expensive, and the degradation efficiency of methylene blue dye is low.
[0004] Coal gasification slag is a solid residue formed by the carbon particles remaining in the coal during the incomplete combustion of coal with oxygen or oxygen-enriched air to generate CO and H2. The inorganic minerals in the coal undergo different physical and chemical transformations, and are mainly composed of silicon dioxide, aluminum oxide, calcium oxide, iron oxide, carbon and other components. According to the particle size, coal gasification slag is divided into coal gasification coarse slag (CGCS) and coal gasification fine slag (CGFS). The residual carbon content of coal gasification fine slag is usually higher than that of coarse slag. Coal gasification coarse slag is produced at the slag discharge port of the gasifier, accounting for a large proportion of about 60% to 80%; coal gasification fine slag is mainly produced in the dedusting device of the synthesis gas, accounting for about 20% to 40%. The main mineral phase of coal gasification fine slag (CGFS) is amorphous aluminum silicate, mixed with quartz, calcite and other crystalline phases. This chemical composition characteristic rich in silicon, aluminum and carbon resources and the special mineral phase composition provide a basis for the recycling of coal gasification fine slag. It should be noted that although coal gasification slag has a variety of applications, its large output, low utilization rate, high processing cost and environmental threats are still serious and gradually become a burden for enterprises. Therefore, when using coal gasification slag, it is necessary to comprehensively consider its environmental impact and resource value and adopt scientific and reasonable processing methods and resource technology. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a coal gasification fine slag doped g-C3N4 photocatalyst and its preparation method and application. CGFS is doped onto the surface of g-C3N4 by calcination method to construct CGFS / g-C3N4 photocatalyst to make up for the defects of g-C3N4 in structure and performance. Under visible light irradiation, CGFS / g-C3N4 photocatalyst can significantly improve the photocatalytic performance and has good stability.
[0006] In order to achieve the above-mentioned invention object, the technical solution adopted is:
[0007] In a first aspect, the present invention provides a coal gasification slag-doped g-C3N4 photocatalyst, comprising coal gasification slag and g-C3N4; the mass ratio of the coal gasification slag to g-C3N4 is (1-5):100.
[0008] In a second aspect, the present invention provides a method for preparing the coal gasification slag doped g-C3N4 photocatalyst described in the first aspect, wherein the coal gasification slag and g-C3N4 are evenly mixed and calcined to obtain the coal gasification slag doped g-C3N4 photocatalyst.
[0009] In some other embodiments, the mass ratio of the coal gasification fine slag to g-C3N4 is (1-5):100;
[0010] Alternatively, the calcination is carried out in an air atmosphere at a heating rate of 1-3°C / min, at 520-550°C, for 3-5h.
[0011] In some other embodiments, the coal gasification fine slag is obtained by vibrating, screening, acid-treating and washing the raw coal gasification slag;
[0012] Preferably, the particle size of the coal gasification fine slag is less than 150 μm, and the acid treatment is carried out for 1-3 hours using an acid with a concentration of 1-5 mol / L and a solid-liquid ratio of 1 g: (10-50) ml;
[0013] Further preferably, the acid treatment is a treatment with 3 mol / L hydrochloric acid at a solid-liquid ratio of 1 g:30 ml for 2 h.
[0014] In some other embodiments, the preparation method of g-C3N4 is to calcine the organic amine at 520-550°C for 5-10h in an air atmosphere at a heating rate of 8-10°C / min.
[0015] In some other embodiments, the organic amine is urea, cyanamide, melamine or melamine.
[0016] In a third aspect, the present invention provides the use of the coal gasification fine slag doped with g-C3N4 photocatalyst described in the first aspect in photocatalytic degradation of organic dye wastewater, preferably, the organic dye is methylene blue.
[0017] In a fourth aspect, the present invention provides a method for degrading methylene blue, using the coal gasification fine slag doped with g-C3N4 photocatalyst as a catalyst and adding it to methylene blue wastewater to catalytically degrade methylene blue under visible light.
[0018] In some other embodiments, the concentration of the methylene blue pollution is 10-40 mg / L, and the added amount of the coal gasification fine slag doped with g-C3N4 photocatalyst is 0.2-1 g / L.
[0019] In some other embodiments, the pH of the methylene blue wastewater is 4-10, preferably, the pH of the methylene blue wastewater is 8-10.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] (1) The coal gasification fine slag used in the present invention has a good pore structure and a high content of residual carbon (15-50%), which provides a good basis for its use as a raw material to prepare functional materials. After acid treatment, most of the metal oxides and a small part of SiO2 contained in CGFS are removed, and the remaining components are mostly residual carbon, which increases the proportion of carbon in CGFS. At the same time, while the acid treatment removes the metal oxides contained in CGFS, the residual carbon has a good pore structure and can be used as a mesoporous material for adsorption purposes, catalysis and electrochemical reactions.
[0022] (2) The coal gasification slag doped g-C3N4 photocatalyst prepared by the present invention reduces the g-C3N4 hole-electron recombination efficiency, realizes effective degradation of methylene blue under visible light, promotes the separation of photogenerated carriers, improves the photocatalytic activity, further increases the degradation efficiency, and is conducive to its practical application in environmental remediation.
[0023] (3) The preparation method of the present invention is simple and easy to control, and the raw materials are widely available, thus broadening the utilization of coal gasification slag. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The infrared spectra of Comparative Example 1 and Examples 1 and 2 of the present invention are shown below;
[0025] Figure 2 The XRD patterns of Comparative Example 1 and Examples 1 and 2 of the present invention are shown below;
[0026] Figure 3 The photocatalytic degradation efficiency diagram of methylene blue of Comparative Examples 1-6 and Examples 1-3 of the present invention;
[0027] Figure 4 This is a diagram showing the efficiency of photocatalytic degradation of methylene blue at different pH values in Example 1 of the present invention;
[0028] Figure 5 This is a diagram showing the efficiency of photocatalytic degradation of methylene blue at different dosages according to Example 1 of the present invention;
[0029] Figure 6 This is a graph showing the degradation efficiency of photocatalytic degradation of methylene blue at different methylene blue concentrations according to Example 1 of the present invention. DETAILED DESCRIPTION
[0030] In order to facilitate those skilled in the art to better understand the scheme of the present invention and make the above-mentioned objects, features and advantages of the present invention more understandable, the present invention is further described in detail below with reference to embodiments.
[0031] 1. Preparation of materials:
[0032] In the following method of the present invention, the instruments and reagents used are as follows:
[0033] Table 1 Instruments and equipment
[0034]
[0035] Table 2 Main reagents
[0036]
[0037] Coal gasification fine slag (CGFS) is the treated coal gasification fine slag (CGFS) obtained by oscillating and screening the original coal gasification slag to select the part with a particle size less than 150μm in a 3mol / L HCl solution at a solid-liquid ratio of 1:30 for 2h, centrifuging and washing with deionized water until neutral. Coal gasification fine slag has a good pore structure and a high content of residual carbon (15-50%), which provides a good basis for its use as a raw material to prepare functional materials. After acid treatment, most of the metal oxides and a small part of SiO2 contained in CGFS are removed, and the remaining components are mostly residual carbon, which increases the proportion of carbon in CGFS. At the same time, acid treatment can remove the metal oxides contained in CGFS while making the residual carbon have a good pore structure, which can be used as a mesoporous material for adsorption purposes, catalysis and electrochemical reactions.
[0038] Embodiment 1:
[0039] Preparation of g-C3N4: 10 g of urea was placed in a covered crucible in a muffle furnace and heated at 550 °C in an air environment at a heating rate of 10 °C / min for 5 h.
[0040] 0.5 g g-C3N4 and 0.015 g CGFS were mixed evenly and ground for 15 min. After mixing evenly, the mixture was placed in a muffle furnace and heated at a heating rate of 3°C / min in an air environment at 550°C for 5 h to obtain a CGFS / g-C3N4 composite catalyst with a CGFS doping ratio of 3%.
[0041] Example 2
[0042] Different from Example 1, 0.5 g g-C3N4 and 0.005 g CGFS were mixed and ground for 15 min, and then placed in a muffle furnace and heated at a heating rate of 3°C / min in an air environment at 550°C for 5 h to obtain a CGFS / g-C3N4 composite catalyst with a CGFS doping ratio of 1%. The other preparation processes were the same as in Example 1.
[0043] Example 3
[0044] Different from Example 1, 0.5 g g-C3N4 and 0.025 g CGFS were mixed and ground for 15 min, and then placed in a muffle furnace and heated at a heating rate of 3°C / min in an air environment at 550°C for 5 h to obtain a CGFS / g-C3N4 composite catalyst with a CGFS doping ratio of 5%. The other preparation processes were the same as in Example 1.
[0045] Comparative Example 1
[0046] The difference from Example 1 is that only g-C3N4 is prepared, and the other preparation processes are the same as those in Example 1; no CGFS doping treatment is performed.
[0047] Comparative Example 2
[0048] Different from Example 1, only CGFS is used without compounding with g-C3N4.
[0049] Comparative Example 3
[0050] The difference from Example 1 is that coal slag is compounded with g-C3N4, and the other preparation processes are the same as those in Example 1.
[0051] Comparative Example 4
[0052] The difference from Example 1 is that the coal gasification slag that has not been treated with acid is directly compounded with g-C3N4, and the other preparation processes are the same as those in Example 1.
[0053] Comparative Example 5
[0054] The difference from Example 1 is that kaolin is directly compounded with g-C3N4, and the other preparation processes are the same as those in Example 1.
[0055] Comparative Example 6
[0056] The difference from Example 1 is that melamine is directly compounded with CGFS, and the other preparation processes are the same as those of Example 1.
[0057] Figure 1 The infrared spectra of Comparative Example 1 and Examples 1 and 2 of the present invention are shown in FIG. Figure 1 It can be seen that at 3000cm -1 Up to 3500cm -1 The absorption peaks observed in the range of 1200 cm-1 are usually associated with the stretching vibration of amino (-NH2) or hydroxyl (-OH). -1 Up to 1650cm -1 In the frequency band, a series of significant absorption peaks are attributed to the stretching vibration of the CN heterocyclic structure, which is a typical feature of the g-C3N4 molecular structure. -1 The absorption peak at corresponds to the out-of-plane bending vibration of the triazine ring, further confirming the existence of the triazine unit in g-C3N4. All of the above confirm the successful synthesis of g-C3N4 material. After g-C3N4 and CGFS are combined, a heterojunction is formed, which leads to the weakening of the characteristic peak of g-C3N4. The weakening of the characteristic peak becomes more obvious with the increase of the doping amount of CGFS. The formation of the heterojunction provides a more convenient migration channel for photoexcited electrons, reduces the recombination between photogenerated electron-hole pairs, and thus improves the photocatalytic performance.
[0058] Figure 2The XRD patterns of Comparative Example 1 and Examples 1 and 2 of the present invention are shown in FIG. Figure 2 It can be seen that the characteristic diffraction peaks of g-C3N4 can be confirmed according to the standard document PDF50-1512 of X-ray powder diffraction (XRD). The XRD spectrum shows that the diffraction peaks of the (100) crystal plane and (002) crystal plane of g-C3N4 correspond to the peaks of 2θ angles of 13.118° and 27.374°, respectively. The XRD spectrum of the composite material CGFS / g-C3N4 shows an obvious diffraction peak at 26.6°, which corresponds to the (101) interface of silica. And with the increase of the GCFS doping amount, the peak area corresponding to the diffraction peak of the silica (101) crystal plane gradually increases, which indicates the successful synthesis of the material.
[0059] 2. Photocatalytic performance:
[0060] The materials prepared in Examples 1-3 and Comparative Examples 1-6 of the present invention were added to methylene blue wastewater with a concentration of 10-40 mg / L at a solid-liquid ratio of 1:5000-5:5000 (g / mL), and the pH of the methylene blue wastewater was 4-10. After being stirred evenly, the methylene blue was degraded under light conditions. Table 1 shows the degradation performance of the photocatalysts prepared in Examples 1-3 and Comparative Example 1 on methylene blue.
[0061] Table 1 Photocatalyst degradation performance of methylene blue
[0062] Serial number First degradation rate Degradation rate after 3 cycles Example 1 96.4% 88.5% Example 2 86.8% 76.3% Example 3 94.6% 85.4% Comparative Example 1 65.6% 48.2%
[0063] As can be seen from Table 1, the photocatalysts prepared in Examples 1-3 showed good stability, and the degradation efficiency only decreased by about 10% after three cycles, indicating that the catalysts prepared by the present invention have a certain degree of reusability. The reason for the performance degradation may be the loss of part of the catalyst during recycling and the partial contaminants remaining in the porous pores hindering partial light absorption.
[0064] Figure 3 The photocatalytic degradation efficiency of methylene blue of Comparative Examples 1-6 and Examples 1-3 of the present invention is shown in FIG. Figure 3It can be seen that compared with undoped g-C3N4, the g-C3N4 photocatalyst doped with coal gasification slag improves the degradation effect of methylene blue, and the effect of coal gasification fine slag doped with g-C3N4 at a doping amount of 3% is better than that of the catalyst with a doping amount of 1%. This is because the g-C3N4 photocatalyst doped with coal gasification fine slag reduces the hole-electron recombination efficiency of g-C3N4. Effective degradation of methylene blue is achieved under visible light, the separation of photogenerated carriers is promoted, the photocatalytic activity is improved, and the degradation efficiency is further increased. Too high a composite amount of coal gasification fine slag will cover the original active sites of g-C3N4, resulting in a slight decrease in catalytic activity. In comparison, the acid-treated CGFS also has certain adsorption due to its rich pore size and pore structure, but its degradation effect is not good, far lower than that of the composite material. The CGFS without acid treatment has a low carbon content and a low porosity, and the degradation effect is not good. Since the g-C3N4 / kaolin composite material basically does not contain carbon, its degradation efficiency is relatively poor. Compared with urea, melamine has a lower ignition loss, but the degradation efficiency of the material obtained by directly using melamine to composite with CGFS is poor. Analysis shows that this may be because secondary calcination can change the morphology, structure and specific surface area of g-C3N4.
[0065] Figure 4 The efficiency diagram of photocatalytic degradation of methylene blue at different pH values in Example 1 of the present invention is shown in FIG. 1 , wherein the pH value of methylene blue wastewater is adjusted to 4-10 by adding HCl or NaOH. Figure 4 It can be seen that under neutral and alkaline environmental conditions (pH 8-10), the degradation efficiency of methylene blue by the photocatalyst doped with g-C3N4 of coal gasification slag is relatively high. As the pH decreases, the degradation efficiency decreases accordingly. Therefore, the photocatalyst doped with g-C3N4 of coal gasification slag prepared by the present invention is more suitable for neutral and alkaline environmental conditions.
[0066] Figure 5 The efficiency diagram of photocatalytic degradation of methylene blue at different dosages of Example 1 of the present invention is shown. When the photocatalyst prepared in Example 1 with different solid-liquid ratios is added to methylene blue wastewater, it can be found that with the increase in the amount of photocatalyst added, the degradation efficiency of the system for methylene blue is gradually enhanced, but too high an amount of addition may cause a decrease in the degradation rate. The reason is that if the catalyst dosage is too small, the catalytic active sites provided are small, resulting in a low decolorization rate; and if the catalyst is too much, the number of methylene blue molecules adsorbed on the surface of the catalyst particles will be relatively insufficient, the catalyst will accumulate, and part of the pore structure will be blocked, affecting the adsorption of methylene blue.
[0067] Figure 6 The degradation efficiency diagram of methylene blue wastewater with different concentrations in Example 1 of the present invention is shown in FIG. Figure 6It can be seen that as the concentration of methylene blue increases, the degradation efficiency of the system for methylene blue gradually decreases. This is because when the mass concentration of the dye increases, the dye adsorbed on the catalyst surface will hinder photons from reaching the catalyst surface, the amount of free radicals generated will decrease, and then the degradation efficiency will decrease.
[0068] Although the above describes the specific implementation mode of the present invention in conjunction with the accompanying drawings, it is not intended to limit the scope of protection of the present invention. Those skilled in the art should understand that various modifications or variations that can be made by those skilled in the art on the basis of the technical solution of the present invention without creative work are still within the scope of protection of the present invention.
Claims
1. A coal gasification slag doped g-C3N4 photocatalyst, characterized in that: It includes coal gasification fine slag and g-C3N4; the mass ratio of the coal gasification fine slag to g-C3N4 is (1-5):
100.
2. A method for preparing the coal gasification fine slag doped g-C3N4 photocatalyst according to claim 1, characterized in that: The coal gasification slag and g-C3N4 are uniformly mixed and calcined to obtain the coal gasification slag doped g-C3N4 photocatalyst.
3. The preparation method according to claim 2, characterized in that: The mass ratio of the coal gasification fine slag to g-C3N4 is (1-5):100; Alternatively, the calcination is carried out in an air atmosphere at a heating rate of 1-3°C / min, at 520-550°C, for 3-5h.
4. The preparation method according to claim 2, characterized in that: The coal gasification fine slag is obtained by vibrating, screening, acid treatment and washing the original coal gasification slag; Preferably, the particle size of the coal gasification fine slag is less than 150 μm, and the acid treatment is carried out for 1-3 hours using an acid with a concentration of 1-5 mol / L and a solid-liquid ratio of 1 g: (10-50) ml; Further preferably, the acid treatment is a treatment with 3 mol / L hydrochloric acid at a solid-liquid ratio of 1 g:30 ml for 2 h.
5. The preparation method according to claim 2, characterized in that: The preparation method of g-C3N4 is to calcine the organic amine at 520-550°C for 5-10h in an air atmosphere at a heating rate of 8-10°C / min.
6. The preparation method according to claim 5, characterized in that: The organic amine is urea, cyanamide, melamine or melamine.
7. An application of the coal gasification fine slag doped with g-C3N4 photocatalyst as claimed in claim 1 in photocatalytic degradation of organic dye wastewater, preferably, the organic dye is methylene blue.
8. A method for degrading methylene blue, characterized in that: The coal gasification fine slag doped with g-C3N4 photocatalyst as claimed in claim 1 is used as a catalyst and added into methylene blue wastewater to catalytically degrade methylene blue under visible light.
9. The degradation method according to claim 8, characterized in that: The concentration of the methylene blue pollution is 10-40 mg / L, and the addition amount of the coal gasification fine slag doped with g-C3N4 photocatalyst is 0.2-1 g / L.
10. The degradation method according to claim 9, characterized in that: The pH of the methylene blue wastewater is 4-10, preferably, the pH of the methylene blue wastewater is 8-10.
Citation Information
Patent Citations
Preparation method and application of visible light response Nb2O5 / g-C3N4 heterojunction material
CN105195203A
Cited By
Gasification slag-based porous geopolymer / g-C3N4 heterojunction photocatalytic microspheres as well as preparation method and application thereof
CN121222468A
A porous geopolymer / g-C3N4 heterojunction photocatalytic microsphere based on gasification slag, its preparation method and application
CN121222468B
Gasification slag-based composite phase hierarchical pore channel photocatalytic material as well as preparation method and application thereof
CN121244267A
Gasification slag-based composite phase multi-level porous photocatalytic materials, their preparation methods and applications
CN121244267B
Porous geopolymer photocatalytic material based on circulating fluidized bed fly ash as well as preparation method and application of porous geopolymer photocatalytic material
CN121244268A